An integrated silicon sensor with microfluidic chip for monitoring potassium and pH - Sharma,S; Radomska-Botelho,Moniz A; Triantis,I; Michelakis,K; Trzebinski,T; Azarbadegan,A; Field,B; Toumazou,C; Eames,I; Cass,A (Microfluidics and Nanofluidics, 2011)
We present ion-sensitive field effect transistor-based sensors, integrated with a microfluidic chip, for monitoring pH and potassium cations. The sensor is strategically located at the base of a well so that the response time of the device depends both on the mean flow through the device and the diffusion coefficient of the analyte being monitored. This would enable monitoring of ions in the presence of larger molecules. The dependence of the device response time on diffusive transport of analytes was examined through a numerical study of the flow field and the passive diffusion of a chemical species. The predicted device response time was compared with the experimental measurements and reasonable agreement found. The general dependence of device response time on geometry, flow rate, and analyte diffusion coefficient was derived. These devices can be used with biological fluids where monitoring of pH and cations provide vital information about the well-being of patients.